The biochemical pathways of apoptotic, necroptotic, pyroptotic, and ferroptotic cell death - Ai, Youwei; Meng, Yutong; Yan, Bo; Zhou, Qinyi; Wang, Xiaodong (Molecular cell, 2024)
Apoptosis, the first regulated form of cell death discovered in mammalian cells, is executed by caspase-3/7, which are dormant in living cells but become activated by upstream caspase-8 or caspase-9 in responding to extracellular cytokines or intracellular stress signals, respectively. The same cell death-inducing cytokines also cause necroptosis when caspase-8 is inhibited, resulting in the activation of receptor-interacting protein kinase 3 (RIPK3), which phosphorylates pseudokinase MLKL to trigger its oligomerization and membrane-disrupting activity. Caspase-1/4/5/11, known as inflammatory caspases, instead induce pyroptosis by cleaving gasdermin D, whose caspase-cleaved N terminus forms pores on the plasma membrane. The membrane protein NINJ1 amplifies the extent of membrane rupture initiated by gasdermin D. Additionally, disturbance of peroxidation of polyunsaturated fatty acid tails of membrane phospholipids triggers ferroptosis, an iron-dependent and caspases-independent necrotic death. This review will discuss how these regulated cell death pathways act individually and interconnectively in particular cell types to carry out specific physiological and pathological functions.